(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1992)
In several Neogene stratigraphic sections of Italy bearing bryozoan assemblages, a great dominance of lunulitiform bryozoans was recorded in those levels characterized by the abundant muddy fraction of the sediment, and by the presence of Heterogeneous Communities. These latter settle and quickly evolve on sea-floors where anomalous sedimentation rates occur, caused by climatic or tectonic factors. Research carried out so far shows that lunulitiform bryozoans may be regarded as insrabiliry indicators, characterizing the early phase of Hererogeneous Communities.